Academic Senate Minutes 2018-05-03 - Academic Senate:::::::::
Agenda approved. Minutes of 8/25/11 approved. Chair Report. Statewide Senator Report. Resolution Honoring Art Warmoth approved for Senate agenda. Chair-Elect Report. EPC Report. Vice President of SAEM Report. CFA Report. FSAC Report. SAC Report. Associated Students Report. Senate Agenda. EPC charged with taking lead on writing policy re: hours and units.